Water Projects And Their Effect In Improving Lattakia City - Wahbi, saleh; saeed , Yazan (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research shows the water resources in Lattakia Governorate represented by the surface water which represents the permanent rivers and the flow basins, in addition to the ground water represented by springs and wells in terms of their geographical distribution, geothermal and hydrological characteristics. and the purpose of the water investment is for irrigation and drinking. The study also showed the methods of investment of water and the most important water Projects the governorate, and the characteristics and hydrographic characteristics of the dams executed and the dams under implementation, and irrigation networks and treatments and drainage networks and their role in development. The study also addressed the prospects of water investment and water projects in the governorate and its role in agricultural, industrial and tourism development and its implication for the population economical and socially, the research concluded with suggestions and conclusions can be used to develop a comprehensive development plan the governorate, This study divided into three main kegissues, it adequately covers all stages of scientific method usually a dopted and follow in geographical research.